3D g-C3N4/WO3/biochar/Cu2+-doped carbon spheres composites: Synthesis and visible-light-driven photocatalytic hydrogen production. (March 2022) - Zhou, Yunlong; Sun, Meng; Yu, Teng; Wang, Jian
Abstract: High surface activity and high-efficiency 3D g-C3 N4 /WO3 /biochar/Cu 2+ -doped carbon spheres (CWB-CuCs) were prepared by a facile one-pot heating method for use as composite photocatalysts. The photocatalysts were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy, X-ray photoelectron spectroscopy, UV–vis diffuse reflectance spectroscopy. The photoelectric properties and mechanism of the photocatalysts were analyzed. The CWB-CuCsphotocatalyst with 40 wt% CuCs showed excellent photocatalytic performance for hydrogen generation (about 6 times better than that of pure g-C3 N4 ). This phenomenon was mainly due to a Z-scheme heterojunction in the biochar between the g-C3 N4 and WO3 . The synergy between the g-C3 N4 /WO3 and CuCs (acting as cocatalysts) increased the electron transfer rate and increased the photocatalytic performance of the composite. Graphical Abstract: ga1 Highlight: 3D g-C3 N4 /WO3 /BC Cu 2+ -doped carbon spheres composites were prepared. The composites exhibited high visible-light photocatalytic hydrogen production. The synergy of g-C3 N4 / WO3 /BC and CuCs improved the photocatalytic activity. As a cocatalyst, the CuCs provided abundant active sites.